Magnesium and manganese affect photosynthesis, essential oil composition and phenolic compounds of Tanacetum parthenium - Farzadfar, S.; Zarinkamar, F.; Hojati, M.
The accumulation of plant defense metabolites is closely associated with the concentration of nutrient elements, yet data related to the interactive effects of two nutrients on the deployment of phenolics and terpenoids are scare. In the present study, the interaction between magnesium (Mg)and manganese (Mn)on nutrient uptake, photosynthesis, oxidative status and the accumulation of phenolics and terpenoids in the leaves of feverfew plants grown at different concentrations of Mg and Mn was investigated. Nutrient uptake and photosynthesis were associated with the amount of applied Mg but could be modified by the concentration of Mn. Phenolic biosynthetic enzymes and individual phenolics were not only induced by Mg, but their levels were also dependent on the Mn supply. Additionally, the proportion of monoterpenes was enhanced by a deficiency of Mg rather than an excess of Mn. Deprivation of Mg also decreased the proportion of sesquiterpenes in the essential oil. Therefore, it appears that a high Mg and a low Mn supply lead to a marked shift from monoterpene to sesquiterpene production. Phenolic compounds also differentially accumulated under varying Mg and Mn concentrations. These results suggest a profound effect of the combined supply of Mg and Mn on the biosynthesis of terpenes and phenolics.
Keywords: ESSENTIAL OIL; FEVERFEW; MAGNESIUM; MANGANESE; PHENOLIC COMPOUNDS